Calcium channel blockers, survival and ischaemic stroke in patients with dementia: a Swedish registry study. (14th September 2020) - Kalar, I.; Xu, H.; Secnik, J.; Schwertner, E.; Kramberger, M. G.; Winblad, B.; von Euler, M.; Eriksdotter, M.; Garcia‐Ptacek, S.
Abstract: Background: The effect of calcium channel blockers (CCB) on mortality and ischaemic stroke risk in dementia patients is understudied. Objectives: To calculate the risk of death and ischaemic stroke in dementia patients treated with CCBs, considering individual agents and dose response. Methods: Longitudinal cohort study with 18 906 hypertensive dementia patients from the Swedish Dementia Registry (SveDem), 2008–2014. Other Swedish national registries contributed information on comorbidities, dispensed medication and outcomes. Individual CCB agents and cumulative defined daily doses (cDDD) were considered. Results: In patients with hypertension and dementia, nifedipine was associated with increased mortality risk (aHR 1.32; CI 1.01–1.73; P  < 0.05) compared to non‐CCB users. Patients diagnosed with Alzheimer's dementia (AD) or dementia with Lewy bodies/Parkinson's disease dementia (DLB‐PDD) taking amlodipine had lower mortality risk (aHR, 0.89; CI, 0.80–0.98; P  < 0.05 and aHR 0.58; CI, 0.38–0.86; P  < 0.01, respectively), than those taking other CCBs. Amlodipine was associated with lower stroke risk in patients with Alzheimer's dementia compared to other CCBs (aHR 0.63; CI, 0.44–0.89; P  < 0.05). Sensitivity analyses with propensity score‐matched cohorts repeated the results for nifedipine (aHR 1.35; 95% CI, 1.02–1.78; P  < 0.05) and amlodipine in AD (aHR, 0.87; CI, 0.78–0.97; P  < 0.05) and DLB‐PDD (aHR, 0.56, 95%CI, 0.37–0.85; P  < 0.05). Conclusion: Amlodipine was associated with reduced mortality risk in dementia patients diagnosed with AD and DLB‐PDD. AD patients using amlodipine had a lower risk of ischaemic stroke compared to other CCB users. Abstract :